Experimental Study on UHPC-Based Grouting Materials and Mechanical Performance of Grouted Splice Sleeve Joints - Fu, Tao; Hou, Jianpu; Zhu, Zhixin; Meng, Lingxiao; Sun, Zhonghua; Wang, Kai; Ren, Xiaoqian (Frontiers in Materials, 2022)
The failure of the assembled structure is mostly due to the weakness of the connection joint. The performance of grouting is a decisive factor for the quality assurance of the whole structure. This paper developed a UHPC grouting material, and its main technical performance was tested. The influence of the grouting mix proportion and anchorage length on the stress performance was summarized through the unidirectional tension test of eight grout-filled splice sleeves. The results show that UHPC grouting containing micro and particles has high strength and durability. UHPC grouting containing steel fibers can further improve the compressive strength and tensile strength. However, it will reduce its fluidity and lead to grouting difficulties, and it is recommended to use UHPC grouting material without steel fibers. The grout-filled splice sleeve joints with UHPC meet the strength requirements, and the sleeve is in the elastic stage in the test, indicating that sleeve joints possess a higher safety margin.